Cyclotide Evolution: Insights from the Analyses of Their Precursor Sequences, Structures and Distribution in Violets (Viola) - Park, Sungkyu; Yoo, Ki-Oug; Marcussen, Thomas; Backlund, Anders; Jacobsson, Erik; Rosengren, K. Johan; Doo, Inseok; Göransson, Ulf (Frontiers in Plant Science, 2017)
Cyclotides are a family of plant proteins that are characterized by a cyclic backbone and a knotted disulfide topology. Their cyclic cystine knot (CCK) motif makes them exceptionally resistant to thermal, chemical, and enzymatic degradation. By disrupting cell membranes, the cyclotides function as host defense by exhibiting insecticidal, anthelmintic, antifouling and molluscicidal activities. In this work, we provide the first insight into the evolution of this family of unique plant proteins by studying the Violaceae, in particular species of the genus Viola. We discovered 157 novel precursor sequences by the transcriptomic analysis of six Viola species: V. albida var. takahashii, V. mandshurica, V. orientalis, V. verecunda, V. acuminata and V. canadensis. By combining these precursor sequences with the phylogenetic classification of Viola, we infer the distribution of cyclotides across 63% of the species in the genus (i.e. ~380 species). Using full precursor sequences from transcriptomes, we show an evolutionary link to the structural diversity of the cyclotides, and further classify the cyclotides by sequence signatures from the non-cyclotide domain. Also, transcriptomes were compared to cyclotide expression on peptide level using liquid chromatography-mass spectrometry. Furthermore, the novel cyclotides discovered were associated to the emergence of new biological functions.